Comprehensive Analysis of Differentially Expressed mRNA, Non-coding RNA, and Their Competitive Endogenous RNA Network of Pacific Oyster Crassostrea gigas With Different Glycogen Content Between Different Environments - Wang, Xue; Wang, Weijun; Li, Zan; Sun, Guohua; Xu, Tao; Xu, Xiaohui; Feng, Yanwei; Luo, Qihao; Li, Bin; Yang, Jianmin (Frontiers in Marine Science, 2021)
Glycogen content is a quantitative trait, its phenotype differences are found between individual oysters due to genetic effects and environmental factors which were including food, water temperature, salinity, and so on. In this study, a full sibling family of Pacific oyster Crassostrea gigas showed different phenotypes with high and low glycogen content between South Huanghai Sea (Rizhao offshore area, RZ) and North Huanghai Sea (Kongtong Dao area, KTD), respectively. At the same time, the content of 11 glucogenic amino acids and 13 fatty acids were also significant differences between RZ and KTD. RNA-seq and small RNA-seq technologies were used for transcriptome sequencing and functional enrichment analysis of differentially expressed RNA were used by Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway. A total of 2,084 mRNAs, 1,080 long non-coding RNAs (lncRNAs), 34 circular RNAs (circRNAs), and 7 microRNAs (miRNAs) were differentially expressed. Based on these differentially expressed genes (DEGs), miRNA target interactions (lncRNA/circRNA–miRNA pairs and miRNA–mRNA pairs) were predicted using the miRanda software. The differentially expressed mRNAs in this network were mainly shown to be involved in calcium signaling pathway and insulin signaling pathway. These findings could help to speculate that environmental factors may be epigenetically regulated by non-coding RNA in C. gigas, thereby further affecting glycogen content.